ON FUNCTIONAL RELATIONS BETWEEN MUNICIPAL AUTHORITIES IN POLAND AND FRANCE - Augustyniak, Monika (Review of European and Comparative Law, 2017)
The article presents the platform of functional relations between the legis-lative body and the executive body of the municipality in the Polish and French legal order . Reflections made in this respect should help improve the model of both bodies of the municipality in the scope of tasks and competences, shaping the platforms of their joint and separate relations . Determining the manner of implementation of tasks and competences of the municipal bodies based on the principle of cooperation should be an aspiration of the legislator to normatively and factually balance the legal status of both municipal bodies . The analysis of the determinants of the functioning of legislative and executive bodies is aimed at proposing directions of changes in their functional relations, in order to increase the efficiency of their operation as the most important determinant of efficient management of the local community.